Associations Between Maltreatment History and Severity of Substance Use Behavior in Youth in Foster Care. (November 2016) - Gabrielli, Joy; Jackson, Yo; Brown, Shaquanna
Substance use (SU) in youth remains a significant public health concern and a risk factor for morbidity and mortality in adolescents. The present study offers examination of the association between severity and chronicity of maltreatment history and SU in youth in foster care. Two hundred and ten (48% female) foster youth with a mean age of 12.71 years ( SD = 2.95 years) completed surveys using an audio-computer-assisted self-interview program. Results revealed 31% of participants reported past-year SU, and substance users had a mean CRAFFT score of 3.43 ( SD = 1.90). Reported age of SU onset was 11.08 years ( SD = 2.21 years). The SU measurement model demonstrated excellent fit in this sample. Accounting for both youth age and youth placement type, the structural model with maltreatment predicting SU severity demonstrated strong model fit with a significant path between maltreatment and SU. Youth in residential facilities and older youth had higher rates of use than those residing in traditional foster home environments and younger youth. Findings provide additional support for the link between maltreatment experiences and SU severity in foster youth and suggest the need for screening and intervention services appropriate for this high-risk population.